The Linkages between Household Consumption and Household Debt Composition in Malaysia - Hammad Ahmad Khan, Hafizah; Abdullah, Hussin; Samsudin, Shamzaeffa (International Journal of Economics and Financial Issues, 2016)
This study intends to examine the relationship between household consumption and household debt composition in Malaysia. Specifically, this study employs the Toda-Yamamoto non-causality test since it is suitable for variables with different levels of integration. Results obtained in this study suggest that the direction of causality runs from consumption to debt. Moreover, the result of the cointegration test also supports that long run relationship exists between the two variables. It also supports the Life Cycle Model, which predicts that a household has been borrowing in order to finance their consumption and expenses. Therefore, this result indirectly suggests that the household has been depending on debt to finance their consumption and thus any negative shocks that occur in the economy can causes serious consequences on the economic performance of the country. Hence, any attempts by policymakers to control the mounting debt level should be focusing on restricting the supply of loans. Keywords: Household debt, Consumption, Causality, Cointegration, Malaysia JEL Classifications: E00, E21, E51